DNA‐Mediated Copper Nanoparticle Formation on Dispersed Single‐Walled Carbon Nanotubes. Issue 8 (August 2015) - Ursu, Elena‐Laura; Clima, Lilia; Hejesen, Christian; Rotaru, Alexandru; Pinteala, Mariana
Abstract A new and facile method for the preparation of single‐walled carbon nanotubes (SWCNTs) decorated with Cu nanoparticles (CuNPs) formed on a double‐stranded DNA template in aqueous solution has been developed. A specially designed synthetic DNA sequence, containing a single‐stranded domain for the dispersion of carbon nanotubes and double‐stranded domains for the selective growth of CuNPs, was utilized. The final SWCNT/CuNP hybrids were characterized using fluorescence spectroscopy and transmission electron microscopy. The analyses clearly demonstrated the selective formation of uniform CuNPs on the carbon nanotube scaffold.